Avaliação do efeito da nanoencapsulação na solubilidade e potencial antioxidante do óleo pigmentado com astaxantina extraída da farinha do resíduo de camarão (Litopeneaus vannamei) - Santos, Renata Nayane Fernandes dos (2024)
Shrimp (Litopenaeus vannamei) is a marine species of great economic importance, and processing produces waste discarded into the environment. In these residues, bioactive compounds such as astaxanthin are present, the primary carotenoid found in shrimp, and have high antioxidant potential. However, the stability and functionality of the carotenoid are lost during the food processing and storage stages. Encapsulation is an effective technique to promote the protection of bioactive compounds such as astaxanthin. This work aims to encapsulate the oil pigmented with astaxanthin obtained from shrimp residue flour to improve solubility and antioxidant potential. The encapsulation technique used was oil/water (O/W) emulsification, using porcine gelatin and soy protein as encapsulating agents and Tween 20 as a surfactant. The formulations developed were: pigmented oil with astaxanthin encapsulated in porcine gelatin (EAG), pigmented oil with astaxanthin encapsulated in soy protein (EAS), pigmented oil with astaxanthin encapsulated in porcine gelatin and soy protein in a 2:2 w/w ratio (EAGS 2:2) and in a 3:1 w/w ratio (EAGS 3:1). The characterization of the particles was carried out by Scanning Electron Microscopy (SEM), Dynamic Light Scattering (DLS), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Zeta Potential (ZP), Dispersion in water, Incorporation Efficiency (IE) of the oil and percentage of astaxanthin in the encapsulates. The Total Antioxidant Capacity (TAC) and Iron Ion Chelation tests were carried out to determine the antioxidant activity. The EAS formulation showed oil leakage and did not follow the characterization steps. The other formulations had a spherical shape and a smooth surface based on the micrographs. The particle size averages by DLS were equal to 159.68 (14.42) nm for EAG, 192.72 (10.44) nm for EAGS 2:2, and 95.41 (17.83) nm for EAGS 3:1. The encapsulated ones presented an amorphous structure based on XRD. By FTIR, an accentuation of the O-H and C-H stretching bands (3314 cm-1, 3291cm-1, 3318cm-1) was observed in EAG, EAGS 2:2, and EAGS 3:1, respectively, revealing chemical interactions between pigmented oil with astaxanthin and the materials used. The IE of the oil was 89.20% (0.31) (EAG), 87.60% (0.13) (EAGS 2:2), and 89.10% (0.30) (EAGS 3:1), where the EAG and EAGS 3:1 did not show a significant difference (p > 0.05). The percentage of astaxanthin incorporated into the encapsulates was approximately 68%, and the dispersibility in water presented values around 50%. The determination of the antioxidant potential indicated that all formulations had the effect of preserving and enhancing the antioxidant activity of the oil, with emphasis on EAGS3:1, which increased the antioxidant potential almost three times in the tests carried out. Therefore, porcine gelatin wall materials and/or combination with soy protein were effective for encapsulating oil pigmented with astaxanthin, as they trapped the oil and increased solubility and antioxidant potential, characteristics that enable incorporation into the food matrix.